A Novel Combined Mother-Infant Clinic to Optimize Post-Partum Maternal Retention, Service Utilization, and Linkage to Services in HIV Care in Rural Rwanda - Guillaine Neza, BSc; Wilberforce Mwizerwa, BA; Jackline Odhiambo, BA; Bethany L. Hedt-Gauthier, PhD; Lisa R. Hirschhorn, MD, MPH; Placidie Mugwaneza, MD, MPH; Jean Paul Umugisha, BA; Felix Rwabukwisi Cyamatare, MD, MPH; Christine Mutaganzwa, MD, MSc; Neil Gupta, MD, MPH (Global Health and Education Projects, Inc., 2017)
Background and Objectives: Despite recent improvements in accessibility of services to prevent mother-to-child transmission of HIV, maternal retention in HIV care remains a challenge in the postpartum period. This study assessed service utilization, program retention, and linkage to routine services, as well as clinical outcomes for mothers and infants, following implementation of an integrated mother-infant clinic in rural Rwanda. Methods: We conducted a retrospective cohort study of all HIV-positive mothers and their infants enrolled in the integrated clinics in two rural districts between July 1, 2012, and June 30, 2013. At 18 months post-partum, data on mother-infant service utilization and program outcomes were reported. Results: Of the 185 mother-infant pairs in the clinics, 98.4% of mothers were on antiretroviral therapy (ART) and 30.3% used modern contraception at enrollment. At 18 months post-partum, 98.4% of mothers were retained and linked back to adult HIV program. All mothers were on ART and 72.0% on modern contraception. For infants, 93.0% completed follow-up. Two (1.1%) infants tested HIV positive. Conclusion and Global Health Implication: An integrated clinic was successfully implemented in rural Rwanda with high mother retention in care and low mother to child HIV transmission rates. This model of integration of services may contribute to improved mother-infant retention in care during post-partum period and should be considered as one approach to addressing this challenge in similar settings. Key words: HIV • Integrated Clinic • Combined Clinic • Antiretroviral Therapy • Post-partum Retention • Linkages • ART • PMTCT • Option B+ • Africa Copyright © 2017 Neza Guillaine et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.affect economic and health promotion.